Perlindungan Harta Bersama dalam Perkawinan Campuran: Analisis Hukum Perdata dalam Perspektif Van zaken - Harry Permana; Fauziah Lubis; Mhd. Yadi Harahap (AHKAM, 2026)
Although mixed marriages have increased in line with population mobility and intensified cross-border interactions, the regulation of the protection of spouses’ community property within differing legal systems continues to raise complex private-law issues. Under Indonesian civil law, the regulation of community property is influenced by principles of Western civil law, including the concept of van zaken, which conceives property as an object of law with specific civil consequences and thus has implications for the status, ownership, and restrictions on certain assets when the spouses hold different nationalities. This study aimed to analyze the protection of community property in mixed marriages under Indonesian civil law using the van zaken perspective. A normative legal research method was employed with juridical-normative and conceptual approaches through a review of legislation, civil law doctrine, and relevant court decisions. The findings show that the protection of community property in mixed marriages largely depends on the existence and formulation of a prenuptial agreement and on a clear separation of assets between husband and wife, thereby clarifying each party’s ownership status over both community property and original (separate) property. The concept of van zaken underscores the importance of clearly determining the legal status of property as an object of law in order to guarantee legal certainty and protection for the parties in mixed marriages. Therefore, there is a need to strengthen regulation, legal practice, and legal understanding concerning community property in mixed marriages so that legal certainty, justice, and protection of the parties’ civil rights can be realized optimally.